ASSESSMENT OF WASTE MANAGEMENT POLICY STRATEGY IN PALANGKA RAYA CITY - Kurniawan S. Utama (Lambung Mangkurat University Press, 2015)
Waste management in Palangka Raya city, which is the responsibility of the Market and Hygiene Agency, is currently facing challenges and problems, such as inadequate infrastructures, small budget allocations, and small revenue from waste retribution. This research is aimed at formulating strategic policies in waste management in Palangka Raya City by analysing currently existing conditions, particularly on asset operational aspects and asset financial aspects.To do so, a descriptive method is used. Strategies are constructed by employing EFI and EFE matrices, quadrant analysis, the strengths-weaknesses-opportunities-threats (SWOT) matrix. Furthermore, the strategies are broken down into programs and action plans.The results showed that the trips of waste transportation using dump trucks are fewer than expected. Only twoof the required three trips per day are currently available. On the other hand, the use of arm-roll trucks is found to meet the standard. Furthermore, budget allocations for operational costs and maintenance costs are still low. Only 1.28 % of the total budget is allocated for purpose. Revenue from waste retribution can only make up 8.72 % of the waste management total budget. Moreover, SWOT analysis has resulted inturn around strategy which has two alternative strategies which include (1) procurement and repairing of waste management infrastructure,and (2) improvement of financing capacity on investment, operation and maintenance in waste management.